… cosa che si cercherà di dimostrare: Referentielle und informationsstrukturelle Beobachtungen zur apposizione grammaticalizzata vom Typ cosa che im Spiegel von Räumlichkeit und Zeitlichkeit - Mayr, Paul; Konecny, Christine (Linguistik Online, 2026)
This article deals with so-called apposizioni grammaticalizzate (‘grammaticalized appositions’) in contemporary Italian which, as will be demonstrated, are text-deictically based and can thus be interpreted as spatial in an abstract sense. The analysis focuses on constructions introduced by the encapsulator cosa che. By considering spoken language data, the paper aims to provide a more comprehensive pragma-syntactic profile of this specific form of appositions, which has so far been primarily associated with ‘conceptional literacy’ (“konzeptionelle Schriftlichkeit” according to Koch/Oesterreicher 1994) in the relevant literature. On the one hand, an alternative interpretation of the construction in terms of information structure will be proposed. On the other hand, oral data from the KIParla corpus are used to illustrate which tendencies in language change seem to be emerging at the contemporary stage of language development. It is argued that the observed processes of change, which reveal speakers’ handling of abstract-spatial references, can be regarded as strategies of Alltagsrhetorik (cf. Stempel 1983), i. e. as ‘rhetorical strategies of everyday life’.